Is the magnesium screw as stable as the titanium screw in the fixation of first metatarsal distal chevron osteotomy? A comparative biomechanical study on sawbones models. (6th September 2021) - Sahin, Adem; Gulabi, Deniz; Buyukdogan, Halil; Agar, Anil; Kilic, Bulent; Mutlu, Ibrahim; Erturk, Cemil
Background: Distal chevron osteotomy (DCO) is commonly performed in hallux valgus surgery. The fixation of the osteotomy is provided by various implants. The usage of biodegradable implants such as magnesium is gradually increasing due to the advantages they provide. In this study, we aimed to compare the fixation of DCO with magnesium or titanium screw biomechanically.Methods: Twenty sawbones were used. The samples were divided into two equal groups, including ten sawbones for fixation with single headless titanium (group-1) or magnesium screw (group-2). DCO and screw fixations were performed on all samples using the same technique. Biomechanical testing was applied to five samples in each group in cantilever and the other five in a physiological configuration using a computer connected to the electromechanical test machine. The obtained data were evaluated using the Shapiro–Wilk test, Student's t-test and Mann–Whitney U test on the IBM® SPSS (Statistical Package for the Social Sciences) V22.0 software. Significance was accepted at the p < 0.05 level.Results: There was no statistically significant difference between the magnesium screw and the titanium screw in terms of maximum force, maximum displacement and stiffness measurements in cantilever and physiological loadings ( p > 0.05 for all).Conclusion: This study found no significant difference in biomechanical stability between the magnesium and titanium screws in DCO fixation on sawbones. Further studies with real bones are needed.